Integrated Approach to Stunting Prevention and Treatment: Catfish Cultivation as a Sustainable Solution in Pujo Basuki Village- Trimurjo District, Central Lampung Regency - Oktaviani, Ika; Sariyanto, Iwan; Riyanto, Riyanto; Mulyani, Roza (Poltekkes Kemenkes Manado, 2024)
Introduction: Stunting is a significant health problem in Indonesia, especially in rural and remote areas. Central Lampung Regency, namely Pujo Basuki Village, has been designated as a stunting locus area since 2022 because the prevalence of stunting is 15.8%. The aim of this activities had to raise public awareness in efforts to reduce and prevent stunting in the Pujo Basuki Village area, Central Lampung, Lampung Province. Method: Through the planning and preparation, implementation and monitoring, evaluation and reporting stages of an integrated approach to preventing and handling stunting through training in catfish cultivation and how to make catfish feed, Providing catfish assistance, nutritional education to residents with stunted children and KEK pregnant women. Results: Training was carried out and the creation of catfish ponds and distribution of catfish seeds at 3 location points in village subsections. It was carried out for 2.5 months. The harvest is given to families with stunted toddlers and pregnant women with KEK. There was an increase knowledge about nutrition and balanced menus for toddlers of cadres and families of stunting from 59% to 80%. Conclusion: Activities are carried out optimally, residents are enthusiastic in increasing their efforts to reduce the incidence of stunting and prevent stunting in the future. Catfish cultivation and education activities will continue in 2024 with the target of creating a processed menu made from catfish to revive the village's creative economy.